Effect of Daily Dose Vs Alternate Day Dose Oral Iron on Improvement in Hemoglobin Levels in Iron Deficiency Anemia in First and Second Trimester of Pregnancy - Qayum, Sana; Rauf, Bushra; Naz, Tahira; Gul, Humera; Gohar, Nayab (Indus Journal of Bioscience Research, 2025)
Background: Iron deficiency anemia (IDA) is a common and significant complication during pregnancy, necessitating effective and well-tolerated treatment strategies. While daily oral iron supplementation is a standard approach, its comparative efficacy against alternate-day supplementation remains an area of ongoing research. Objective: To compare the efficacy of daily oral iron dose and alternate oral iron dose for the treatment of IDA in first and second trimester of pregnancy. Study Design: Randomized controlled trial. Duration and Place of Study: The study was conducted from May 2024 to November 2024 at the Obstetrics and Gynecology Department, Hayatabad Medical Complex, Peshawar. Methodology: A total of 296 pregnant women aged 15–40 years with singleton pregnancies (≤24 weeks gestation) and diagnosed with IDA were randomized into two groups. Group A received daily ferrous fumarate (350 mg) for eight weeks, while Group B received the same dose on alternate days. Weekly monitoring was performed, and hemoglobin levels were reassessed after eight weeks. Efficacy was defined as a hemoglobin increase of ≥2 g/dL. Results: In Group A, 28.4% of patients achieved the defined efficacy, compared to 13.5% in Group B (p=0.002). Stratification analyses revealed significant efficacy differences favoring Group A in patients aged 15–30 years (p=0.004), with gestational age ≤15 weeks (p=0.005), and BMI >25 (p=0.012). No significant differences were observed for older patients, later gestational age, or lower BMI categories. Conclusion: Daily oral iron supplementation is significantly more effective than alternate-day dosing in treating IDA during pregnancy, particularly in younger women.